2019
DOI: 10.1371/journal.pone.0221158
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of low-acuity cases referred for emergency ambulance dispatch following ambulance service secondary telephone triage: A retrospective cohort study

Abstract: Objective Ambulance-based secondary telephone triage systems have been established in ambulance services to divert low-acuity cases away from emergency ambulance dispatch. However, some low-acuity cases still receive an emergency ambulance dispatch following secondary triage. To date, no evidence exists identifying whether these cases required an emergency ambulance. The aim of this study was to investigate whether cases were appropriately referred for emergency ambulance dispatch following second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…14 This study's result is lower than that found for the London metropolitan area, where 38%, were not in need of emergency assistance and not conveyed. 8 However, it was higher than that reported by Eastwood et al, 13 where 17.7% of cases were not conveyed by ambulance emergency and were inappropriate. Furthermore, our results showed a high percentage (71.86%) of patient/relative-initiated decisions for all nonconveyed cases.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…14 This study's result is lower than that found for the London metropolitan area, where 38%, were not in need of emergency assistance and not conveyed. 8 However, it was higher than that reported by Eastwood et al, 13 where 17.7% of cases were not conveyed by ambulance emergency and were inappropriate. Furthermore, our results showed a high percentage (71.86%) of patient/relative-initiated decisions for all nonconveyed cases.…”
Section: Discussionmentioning
confidence: 69%
“…8 A recent report indicated that 17.7% of cases were not conveyed by ambulance. 13 Moreover, Breeman et al reported that nearly 26.2% of ambulance runs resulted in nonconveyance. 14 Phillips et al described reasons for nonconveyance of probable patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, anyone can call 1-1-9 for free access to an ambulance. In other countries such as Australia, the telephone triage service is used to triage the call and then transfer it to the ambulance dispatch center ( 8 , 10 ). To make telephone triage service more effective, it may be necessary not only to educate the public but also to change the social system for calling for an ambulance.…”
Section: Discussionmentioning
confidence: 99%
“…Eastwood et al revealed that planned emergency department (ED) visits were more likely to be ED suitable than unplanned ED visits (OR 1.62; 95%CI: 1.5–1.7) ( 8 ). Another study revealed that all secondary telephone triage cases referred for emergency ambulance dispatch had transportation rates higher than all metropolitan emergency ambulance cases (82.2% vs. 71.1%) ( 10 ). However, the effect of the telephone triage service on the EMS system has not been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“… 1 In 2018–2019, this secondary triage service diverted 15.6% (114 589 cases) of AV’s workload to alternative healthcare providers or home care, or following secondary triage, returned other cases for emergency ambulance dispatch (secondary dispatch). Research has shown that secondary dispatch cases had paramedic treatment rates similar to direct dispatch cases, 2 and were significantly more appropriate for the emergency department (ED). 3 Older adult patients are frequent users of ambulance services 4 ; however, little is known about their secondary triage usage and the appropriateness of the referral of these patients back into the emergency care pathways.…”
Section: Introductionmentioning
confidence: 99%